Drag Coefficient during Strong Typhoons - Binglan Wang; Lili Song; Wenchao Chen (Advances in Meteorology)
Using data from wind towers during typhoons Hagupit and Nuri, drag coefficient was estimated. The relationship between drag coefficient and atmospheric stability was examined. The results indicate that the drag coefficient decreased when atmosphere stability changed from weakly stable or unstable to neutral. Relationship between drag coefficient and wind speed was also examined, and the results indicate that the relationships between drag coefficient and wind speed were similar to other researchers’ result, but the wind thresholds were different due to different observation sites. Quantitative expressions between drag coefficient and wind speed were derived.